Buzzing beyond honey How diversification and processing are transforming beekeeping - Singh, Vinay; Singh, Gurdeep; Buttar, Tejbir Singh (Indian Farming, 2025)
Beekeeping has evolved from a traditional honey-centric practice into a multifaceted enterprise, thanks to innovative approaches in product diversification and value addition. This case study chronicles the journey of Jagtar Singh, a progressive beekeeper from Punjab, who transformed his subsidiary beekeeping occupation from a modest honey and wax production unit into a thrivingenterprise producing diversified products such as pollen, pollen-based beverages, and beeswax-based creams and soaps. Guided by technical support from Punjab Agricultural University, Ludhiana and Krishi Vigyan Kendra, Bathinda, Jagtar acquired advanced training, adopted processing techniques, and sustainable practices to innovate and expand his operations. His emphasis on branding,retailing, and quality enhancement has enabled him to improve profitability and resilience in the face of challenges like fluctuating hive numbers and market dynamics. By moving beyond honey, this inspiring story highlights the immense potential of value addition and product innovation in beekeeping to foster rural prosperity and entrepreneurship.